Effect of Soybean Protein Isolate and Tea Polyphenol Stabilized High Interior Phase Pickering Emulsion Replacing Fat on Meatball Quality - Shuping LIU; Xiuwen PENG; Jiamei ZHANG; Peizhao LI (Shipin gongye ke-ji, 2024)
In order to reduce the harm caused by high intake of saturated fat on human health. This study aimed to investigate the effect of high interphase Pickering emulsions (HIPEs) stabilized by soybean protein isolated and soybean oil, and tea polyphenols were used as functional ingredients to evaluate two different HIPEs as pork back fat (PBF) replacers in the meatballs. Six different formulations were prepared by the replacement of PBF with water, HIPEs and HIPEs loaded with tea polyphenols. Physical, chemical and sensory indexes of meatballs were assessed. Compared with the control group, there were significant differences in all indexes expect pH (P<0.05). Reduce-fat meatballs with HIPEs showed higher cooking rate (93.59%), content of moisture (66.91%) and protein (14.48%) and lower content of fat (8.42%). The hardness, elasticity, cohesiveness and chewability of meatballs increased with the addition of emulsion. After addition of HIPEs, the L* of meatballs was increased, and the a*, b* were increased due to the addition of tea polyphenols. The HIPEs loaded with tea polyphenols had the best improvement on the infiltrate on the moisture (1.57%) and fat (0.019%) of meatballs, the lowest TBA value was 4.12 mg/kg. The sensory evaluation was higher than the control group. Using HIPEs as a fat substitute could effectively reduce the fat content in meatballs and improve the yield and quality of meatballs. This study can provide some reference for the development of fat-reducing meat products.